Normally transparent smart window with haze enhancement via inhomogeneous alignment surface. Issue 3 (19th February 2019) - Meng, Cuiling; Tseng, Man Chun; Tang, Shu Tuen; Zhao, Chen Xiang; Yeung, Sze Yan; Kwok, Hoi Sing
ABSTRACT: Smart windows which switch between transparent and scattering states can be used not only as privacy window in buildings and cars, but also as information displays, and motorcycle helmet visors. Here, we have proposed a reverse mode polymer-stabilised liquid crystals (PSLCs) smart window based on inhomogeneous alignment surface, which greatly enhances the haze by 42% when compared to device without inhomogeneity treatment. A 100-cm 2 window that switches between the power-off clear state (~4% haze) and a power-on scattering state (64% haze at 15 V) in less than 3.5 ms is demonstrated. Since no high-temperature treatment (< 80°C) is involved in device fabrication, further development on plastic films is feasible. Graphical Abstract: